Малоинвазивные методы лечения пульпита (LLC "Endo Press", 2020)
Experiments on the pulp of rats teeth have shown that these preparations for a direct covering stimulate the formation of replaceable hard connecting tissue and prevent the diffusion inflammation on the area of root pulp. Clinical tests have shown high efficiency of the method of vital amputation of tooth pulp in treating pulpitis.